Recent Publications (Quarterly Journal of Economics, 1968)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 82, Issue 1, February 1968, Pages 168–173, https://doi.org/10.1093/qje/82.1.168 Published: 01 February 1968